The Efficacy Of Glass Ionomer Hybrid As Orthodontic Brackets Adhesives To Inhibit Calsium Released Of The Enamel - Rina Sutjiati (Universitas Muhammadiyah Yogyakarta, 2012)
Composite resins are predominantly used to bond orthodonticbrackets onto teeth. These can lead to calcium released of the enamel surroundingthe brackets. Purpose : To observe calcium release during the use of adhesiveswhich release fluoride Method : This experimental study was design to determinethe calcium released after soaking in the acid solution. This in vitro study usedforty extracted human premolars (20 teeth were bonded with glass ionomer, and20 teeth were bonded with glass ionomer hybrid). Half of the teeth in each groupwere treated with fluoride application and the other half were not treated fluorideapplication topically. Calcium released of the enamel was evaluated usingSpectrofotometer. Result :The results showed that there was a significantdifference between glass ionomer group without and with fluoride application(p0,005), and there was not significant difference (p0,005) in the group of glassionomer hybrid without and with fluoride application topically. Conclusion :Theadhesive glass ionomer hybrid could prevent calcium released with or without theusage of sodium fluoride.